Case Report: Adrenal Epithelial Cyst in an 11-Year-Old Leptailurus Serval - Devereux, Sacha L.; Baltzer, Wendy I.; Piripi, Susan A.; Owen, Mark C. (Frontiers in Veterinary Science, 2022)
Case Description - A serval (Leptailurus serval) presented for progressive enlargement of the right adrenal gland, which had been found incidentally on abdominal ultrasound 2-years previously and upon subsequent ultrasound examinations enlarged progressively from 1.26cm to 1.43cm. Clinical Findings - Clinical signs had not been recorded by the zookeeper, however progressive weight gain and lethargy were reported. Computed tomography (CT) confirmed the presence of a right caudal pole adrenal mass measuring 1.8 cm. Treatment and Outcome - The right adrenal with associated mass was surgically resected via a ventral midline laparotomy including resection of the right phrenicoabdominal vein in association with the mass. Histopathological examination identified the mass as an epithelial cyst. Chromogranin A staining for a possible pheochromocytoma was performed but was negative. The serval recovered at the zoo without complication and has been on display for 18 months. Clinical Relevance - Epithelial adrenal cysts have not been previously reported in felids. An adrenal cyst should be included on the differential list for any animal with an enlarged, slowly growing adrenal gland mass with non-specific clinical signs.